PENGUATAN LITERASI SEJARAH MELALUI HISTORICAL INQUIRY: BELAJAR DARI SINGAPURA - Armiyati, M.Pd, Laely; Purwanta, Hieronymus (Universitas Indraprasta PGRI, 2024)
Historical literacy is currently one of the goals of history learning in the National Curriculum. This term is not widely known by history teachers in Indonesia, so there is confusion in its application. Singapore, as a country with a high level of literacy, provides directions for using historical inquiry in history learning. This research aims to identify the definition of historical literacy, strategies for strengthening historical literacy, and how to apply historical inquiry to strengthen historical literacy. This research uses a qualitative approach with library study data collection techniques, as well as data analysis using content analysis. The documents used are the Singapore secondary school syllabus issued in 2021, as well as articles containing history and literacy. The results of the first research state that historical literacy is not just reading texts, but analyzing and criticizing historical texts. Second, strategies for strengthening historical literacy can be carried out by using documents (primary and secondary sources) and then asking students to analyze them, or with the help of films combined with learning models. Third, historical inquiry is a learning model listed in the Singapore Curriculum which aims to make students truly feel like they are historical researchers. There are four phases that students need to go through in this model, namely provoking curiosity, collecting data, practicing argumentation, and reflective thinking. These four phases are a series of cycles that will train students to